Success Rate of Common Bile Duct Stones Extraction on First ERCP Attempt - Abdul Samad (Journal of the Dow University of Health Sciences, 2019)
Objective: To determine the success rate of common bile duct stones extraction on first endoscopic retrograde cholangiopancreatography (ERCP) attempt among patients with suspected choledocholithiasis.